Analysis of employee performance in wood processing companies: The role of competence, occupational safety and health, perceived organizational support, and employee engagement - Feli Pramita Andraeni; Suyoto Suyoto; Fatmah Bagis; Nawalin Nazah (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the effect of competence, occupational safety and health, perceived organizational support, and employee engagement on employee performance in wood processing companies. The study employed a quantitative approach by distributing questionnaires to 125 production employees with a minimum of one year of work experience. Data were analyzed using SmartPLS 3.0 to assess the measurement model and examine the relationships among variables. The findings indicate that competence does not directly influence employee performance, whereas occupational safety and health, perceived organizational support, and employee engagement have a positive effect on performance. The model explains 68.4% of the variance in employee performance, highlighting the importance of organizational and psychological factors in enhancing performance. This study is limited to a single industry and relies on self-reported data. Future research is encouraged to apply different analytical approaches, expand respondent characteristics, and use more varied measurement instruments to provide more comprehensive insights. Keywords: Competence; Occupational Safety And Health; Employee Engagement; Perceived Organizational Support; Employee Performance